Sources of omega-6 fatty acids do not alter the rumen degradation and transit of fibre from dairy cow diets - Bettero, V. P.; Gandra, J. R.; Nunes, H. V.N.; Freitas, J. E.; Barletta, R. V.; Carvalho, M. V.; Detmann, E.; Pereira, J. C. (The Kielanowski Institute of Animal Physiology and Nutrition, PAS, 2013)
The objective of this study was to evaluate the behaviour of fibre in the digestive tract on the basis of the passage kinetics of forage and concentrate particles in cows fed different omega-6 fatty-acid sources. The scientific hypothesis of this study was that omega-6 fatty acids do not interfere with the digestion of fibre in the diets of dairy cows. Five primiparous lactating Holstein cows were used in the experiment. The experimental diets were: control (C), ground soyabean (GS), cottonseed (CS), soyabean oil (SO), calcium salts of fatty acids (CSFA). The global mean estimates for the parameters of passage rate (y) were 0.038 and 0.055 h-1 for forage and concentrate, respectively. The only significant effect with respect to the passage rate was a high negative correlation between the concentrate passage rate and dry matter intake. There was less undegradable neutral detergent fibre NDF in treatments without added lipid. Dietary supplementation with lipid sources does not alter the kinetic parameters of roughage and concentrate particle passage or in vitro NDF degradation. Sources of omega-6 fatty acids do not alter the rumen degradation and transit of fibre.
Keywords: Dairy cows; Neutral detergent fibre; Omega-6 PUFA, lipid sources, ruminal kinetics